Acetylcysteine in paracetamol poisoning: a perspective of 45 years of use. Issue 4 (3rd May 2019) - Bateman, D. Nicholas; Dear, James W.
Graphical Abstract: Abstract: Paracetamol poisoning was first reported in 1966. The development of antidotes followed within 10 years, and by 1980 acetylcysteine (NAC) was acknowledged as the optimal therapy available. This article examines the history of the development of NAC and recent developments in its use. We offer suggestions for improvements in the way NAC may be administered and outline new developments that should have major impacts on the way we manage paracetamol poisoning in the near future.